THE DOMESTIC VIOLENCE ACT 116 OF 1998: OFFENCES, DEFENCES, ECONOMIC ABUSE, IMMINENT HARM AND THE CRIME OF DOMESTIC ABUSE– WHAT IS NEW? - Sibisi, Siyabonga (Obiter, 2023)
Recent tragedies relating to gender-based violence have drawn attention to the current state of our relevant law. This article focuses on domestic violence – a species of gender-based violence. It assesses the current state of the Domestic Violence Act 116 of 1998; in particular, it focuses on the offences and defences, as well as on the definition of economic abuse and the concept of imminent harm in relation to domestic abuse. The proposals to amend the definition of these concepts have culminated in the passing of the Domestic Violence Amendment Act 14 of 2021. The bulk of the amendments have not commenced. Nevertheless, this article also comments on the impact that these amendments will have on the thesis of this article. It also sheds some light on the proposed stand-alone crime of domestic abuse.